2020
DOI: 10.3390/nu12020461
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes are Associated with the Programming of White Adipose Tissue Browning Features by Resveratrol and Nicotinamide Riboside Neonatal Supplementations in Mice

Abstract: Neonatal supplementation with resveratrol (RSV) or nicotinamide riboside (NR) programs in male mice brown adipocyte-like features in white adipose tissue (WAT browning) together with improved metabolism in adulthood. We tested the involvement in this programming of long-term epigenetic changes in two browning-related genes that are overexpressed in WAT of supplemented mice, Slc27a1 and Prdm16. Suckling mice received orally the vehicle, RSV or NR from postnatal days 2-to-20. After weaning (d21) onto a chow diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…The pellet was then dissolved with 50 µ l TE buffer pH 8. The bisulfite-converted protocol was carried out using the Zymo EZ DNA Methylation-Gold kit® catalog D5005 [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pellet was then dissolved with 50 µ l TE buffer pH 8. The bisulfite-converted protocol was carried out using the Zymo EZ DNA Methylation-Gold kit® catalog D5005 [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…e alcohol is then discarded, and the tube is allowed to dry by turning it over the tissue until the alcohol evaporates. e pellet was then dissolved with 50 µl TE buffer pH 8. e bisulfiteconverted protocol was carried out using the Zymo EZ DNA Methylation-Gold kit ® catalog D5005 [43,44].…”
Section: Preparation Of Dna and Bisulfite-treated Genomic Dnamentioning
confidence: 99%
“…For instance, clinical studies revealed that obesity-related metabolic parameters such as T2D status and BMI are closely associated with WAT DNA methylation ( 34 , 35 , 36 , 37 , 38 ). Studies using various mouse models with impaired DNA methylation further indicate the crucial roles of DNA methylation in WAT inflammation, WAT insulin resistance, and browning ( 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ).…”
Section: Epigenetic Modifications Of Wat In Obesitymentioning
confidence: 99%
“…Studies using various mouse models with impaired DNA methylation further indicate the crucial roles of DNA methylation in WAT inflammation, WAT insulin resistance, and browning ( 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ).…”
Section: Epigenetic Modifications Of Wat In Obesitymentioning
confidence: 99%
“…[10,12,21] Despite this, [15] the mechanisms accounting for the broad spectrum of their health benefits are still poorly understood. Compelling data indicate that NAD + -raising strategies induce beiging in vivo; [22][23][24] however, the favorable contribution of nicotinamide (NAM), as an NAD + precursor, to adipose energy metabolism and beiging has not been previously assessed in vivo.…”
Section: Introductionmentioning
confidence: 99%